The shack : a novel - Young, William P. (Newbury Park, Calif. : Windblown Media, 2007)
Mackenzie Allen Phillips' youngest daughter, Missy, has been abducted. Evidence that she may have been brutally murdered is found in an abandoned shack deep in the Oregon wilderness. Four years later in the midst of his Great Sadness, Mack receives a suspicious note, apparently from God, inviting him to that shack.
A confluence of paths -- The gathering dark -- The tipping point -- The great sadness -- Guess who's coming to dinner -- A piece of "pi" -- God on the dock -- A breakfast of champions -- A long time ago, in a garden far, far away -- Wade in the water -- Here come da judge -- In the belly of the beasts -- A meeting of hearts -- Verbs and other freedoms -- A festival of friends -- A morning of sorrows -- Choices of the heart -- Outbound ripples -- After words.
Keywords: Life change events -- Fiction; Missing children -- Fiction; Oregon -- Fiction; Religious fiction; Suspense fiction